Des acteurs et des pratiques en toxicomanie : Les enjeux de la participation à un stage de réinsertion socioprofessionnelle - Boivin, Marie-Denyse (Canadian Journal of Counselling and Psychotherapy, 2007)
This study analyzes the factors that influence the perseverance of substance abusers in a vocational rehabilitation training program. Thirty-nine people were interviewed on four different occasions in order to determine their perseverance. Two general observations can be made: 1) most of the participants who did not persevere present several factors of fragility, especially in regard to their capacity for abstinence and their judicial profile, whereas those who persisted present a less complex profile; 2) the participants who persevered are those who were able to establish a significant trainer-trainee relationship. However, those who did not persevere still gained from their stay in the rehabilitation program, especially concerning their capacity for abstinence.